2017
DOI: 10.1111/mec.14329
|View full text |Cite
|
Sign up to set email alerts
|

Mind the cell: Seasonal variation in telomere length mirrors changes in leucocyte profile

Abstract: Leucocytes are typically considered as a whole in studies examining telomere dynamics in mammals. Such an approach may be precarious, as leucocytes represent the only nucleated blood cells in mammals, their composition varies temporally, and telomere length differs between leucocyte types. To highlight this limitation, we examined here whether seasonal variation in leucocyte composition was related to variation in telomere length in free-ranging mandrills (Mandrilllus sphinx). We found that the leucocyte profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…As such, we believe that other explanations for the discrepancy in results among long‐term studies on wild populations deserve further investigation. Studies on birds, for example, measure erythrocyte telomere length, while studies on mammals measure leucocyte telomere length, and it cannot be excluded that these tissues differ in their telomere dynamics (Beaulieu, Benoit, Abaga, Kappeler, & Charpentier, ). Moreover, little is known about the dynamics of interstitial telomeric DNA, which is included in qPCR measures of telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we believe that other explanations for the discrepancy in results among long‐term studies on wild populations deserve further investigation. Studies on birds, for example, measure erythrocyte telomere length, while studies on mammals measure leucocyte telomere length, and it cannot be excluded that these tissues differ in their telomere dynamics (Beaulieu, Benoit, Abaga, Kappeler, & Charpentier, ). Moreover, little is known about the dynamics of interstitial telomeric DNA, which is included in qPCR measures of telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…Second, individuals exhibited higher nematode richness during the long dry season, especially the juveniles (Poirotte et al, 2016)-although our analyses show that gut parasites do not explain fecal neopterin levels. Third, the oxidative damages of females, including juvenile females, were found to be higher during the long dry season (Beaulieu et al, 2014), whereas their leucocyte profiles also varied seasonally, with lower lymphocyte proportion being observed during the long dry season, presumably because of the stress at that time of the year (Beaulieu et al, 2017) which is also characterized by increases in cortisol production compared to the long rainy season-although the highest cortisol concentrations are in fact observed during the short dry season (Charpentier et al, 2018). It is therefore likely that the long dry season poses a particular challenge on the immune system of juvenile mandrills, due to combined effects of nutritional stress and higher disease risk, which is reflected by the effect of the mating season (or proportion of cycling females) on neopterin levels.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies in humans have shown that the rate of telomere attrition and telomerase activity are significantly different between cell types, suggesting cell-specific susceptibility and telomere length regulation mechanisms [23,24]. Even more, it has been recently shown in a wild mammal (mandrill, Mandrillus sphinx) that leucocyte composition varies temporally and that these variations are mirrored by change in blood telomere length [25]. Thus, any conclusion based on whole blood or total white blood cells is likely to be biased, especially in the case of infections that affect white blood cell count and composition [26].…”
Section: What To Measure?mentioning
confidence: 99%